Hydrogen recovery from the reforming gas using commercial activated carbon - Rahmanian, Mehdi (2014)
Hydrogen recovery from reforming gas products was investigated using commercial activated carbon in an adsorption column. The commercial activated carbon obtained from market that used for drinking water treatment was applied in this work. In the first part of this study, the effect of treated process of activated carbon by acetic acid, ammonia and steam on hydrogen recovery was studied. In the adsorption study, pressure was increased from atmospheric pressure 1 to 6 bar to investigate the amount of gas adsorbed on fresh activated carbon. In the desorption study, the effects of decreasing pressure was investigated as well. The effect of particle size on the efficiency of hydrogen recovery was emphasis in this study. The results from the experiments indicated that commercial activated carbon was a good candidate for hydrogen recovery because no hydrogen that was adsorbed by activated carbon during our experiments. The recovery of hydrogen was improved to 30.64% and CO2 was the highest adsorbed compared other gases. The results proved that, a small particle size (171 ) has better performance in comparison to other particle sizes. The activated carbon treated with steam showed the best performance on the hydrogen recovery.